Glass-Ionomer Cements in Dentistry-An Update - Dr. Duran Kala, Dr. Niladri Maiti, Dr. AlisirBabakuliyev (International Journal of Advanced Science and Technology, 2020)
This article is an updated review on glass-ionomer cements and covers their structure, properties and clinical uses within dentistry, with an emphasis on its modifications. Glass-ionomers are shown to set by an acid-base reaction within 2–3 min and to form hard, reasonably strong materials with acceptable appearance, release fluoride and are bioactive, so that they gradually develop a strong, durable interfacial ion-exchange layer at the interface with the tooth, which is responsible for their adhesion. Modified forms of glass-ionomers, namely resin-modified glass-ionomers and glass carbomer, are also described and their properties and applications covered.